Comparison of Different Liver Test Thresholds for Drug-Induced Liver Injury: Updated RUCAM versus Other Methods - Yang, Hongyi; Guo, Daihong; Xu, Yuanjie; Zhu, Man; Yao, Chong; Chen, Chao; Jia, Wangping (Frontiers in Pharmacology, 2019)
According to the updated Roussel Uclaf Causality Assessment Method (RUCAM), drug induced-liver injury (DILI) is currently defined based on thresholds of alanine aminotransferase (ALT) levels above 5 × the upper limit of normal (ULN) and/or alkaline phosphatase (ALP) levels greater than 2 × the ULN. However, many parameters with different thresholds are also currently used in the clinic. We therefore performed a comparative analysis to evaluate which set of criteria was the most appropriate to detect DILI. We enrolled hospitalized patients who received fluoroquinolones to treat or prevent infections. Three liver test criteria were used to diagnose DILI in these patients. RUCAM criteria were defined as the gold standard, and other two criteria were 1) ALT or aspartate aminotransferase (AST) levels greater than 5 × the ULN on two consecutive occasions and/or ALP levels greater than 2 × the ULN on two consecutive occasions (issued by drug-induced liver injury network, DILIN); 2) ALT levels greater than 1 × the ULN on two consecutive occasions or ALT levels greater than 2 × the ULN (issued by the National Medical Products Administration, NMPA of China). We found that the RUCAM criteria resulted in 657 warnings, DILIN criteria resulted in 358, NMPA criteria resulted in 1,377, and the positive predictive value (PPV) were 9.74%, 10.89% and 9.73% (P=0.80), respectively. The levels of agreement of the DILIN and NMPA criteria with the RUCAM criteria were moderate, but the agreement between the DILIN criteria and NMPA criteria was poor. In conclusion, the NMPA criteria with relatively lax thresholds for the parameters, require much more labor to determine the diagnosis, making them unsuitable for clinical practice. Conversely, the DILIN criteria employing stricter thresholds for the parameters were more effective but would miss some positive cases and the cases it identified were usually quite serious, which is not conductive to early intervention. Therefore, we still recommend the use of the RUCAM criteria in clinical practice.